Efficient design and hardware implementation of a secure communication scheme for smart grid - Abbasinezhad‐Mood, Dariush; Nikooghadam, Morteza (International journal of communication systems, 2018)
Summary In smart grid, bidirectional communications between the smart meters and control center are subject to several security challenges. Since the smart meters have limited storage space and processing capability, the suggested communication scheme not only must consider the security requirements but also should put the least possible burden on the smart meters' resources. In 2014, an interesting communication scheme has been proposed for the secure consumption reports transmission of the smart meters to the neighbor gateways. In this paper, we first show that this scheme is vulnerable to the smart meter's memory modification, pollution, and denial of service attacks; then, we propose an authenticated communication scheme, which not only is secure against the aforementioned attacks, but also is much more efficient in terms of storage space, communication overhead, and computational complexity. Moreover, our scheme also presents the details of control messages transmission from the neighborhood gateways to the smart meters. Our comparative analysis with several recently published schemes indicates that the proposed scheme is more suitable than the previous ones. More significantly, our realistic implementation on ATmega2560, as a suitable candidate to be used for the smart meters, confirms our claim. In this paper, we have proposed an efficient authenticated communication scheme that can be used for secure bidirectional communications of smart meters and neighborhood gateways. The proposed protocol benefits from dramatic reduction in storage space, communication overhead, and computational complexity. More significantly, our implementation on ATmega2560, as a suitable candidate to be used for the smart meters, confirms our claim.